Effect of neat and binary vehicle systems on the solubility and cutaneous delivery of piperine - Abdullah Hasan Alomrani; Faisal Ibraheem Alhazza; Khalid Mohammed AlGhamdi; Gamal Mohamed El Maghraby (Elsevier, 2018)
Vitiligo is a skin disease characterized by depigmentation disorders due to lack of melanin production. Piperine, an alkaloid extracted from black piper, is active in melanocytes proliferation. To achieve this, the drug has to reach the melanocytes which exist in the deep layer of the epidermis. Higher drug concentration can be obtained after application of optimized formulation to skin. Accordingly, the aim of this work is to investigate the effect of vehicles on skin penetration of piperine as the first step in development of optimized formulation. The tested vehicles include ethanol (Eth), propylene glycol (PG), polyethylene glycol 400 (PEG), and oleic acid (OA) and their combinations. Water was used as the control and skin permeation was monitored using rabbit ear model skin. The highest piperine solubility (48.6 mg/ml) and flux (40.8 μg/cm2 h) was achieved by Eth and the lowest piperine flux (1.17 μg/cm2 h) was reported for PEG. PG and OA showed piperine flux values comparable to that of the control. Among different combination systems, Eth-OA (75:25) binary system had the highest piperine flux (59.3 μg/cm2 h) followed by Eth-OA (50:50) (32.3 μg/cm2 h) and PG-OA (90:10) (22.7 μg/cm2 h). The study thus introduced a vehicle system as the first step in the development of topical formulation of piperine.